In vitro assessment of the antimicrobial activity of tetracycline hydrochloride diluted in three different vehicles against Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum - Andrea Escalante-Herrera; Margarita Chaves; Jean Carlos Villamil; Nelly Stella Roa (Wolters Kluwer Medknow Publications, 2022)
Background: The development and progression of periodontal diseases is a result of the dynamic interaction of microorganisms within their habitat, and changes in this habitat generate a dysbiotic state. Fusobacterium nucleatum and Prevotella intermedia are bridging microorganisms between the pioneer communities and other microorganisms responsible for periodontitis such as Porphyromonas gingivalis. Tetracycline hydrochloride (TTC-HCl) is commonly used as a coadjutant in periodontal treatment in the form of an antiseptic. However, there are no clear dilution or concentration protocols. Objective: This study aimed to evaluate the in vitro antimicrobial activity of TTC-HCl diluted in sterile water, saline solution, and 2% lidocaine with epinephrine 1:80,000 at concentration of 125, 250, and 500 mg, at three time points- 30, 60, and 120 s - on P. intermedia, F. nucleatum, and P. gingivalis using the Kelsey-Maurer technique. Materials and Methods: The antimicrobial activity of TTC-HCl was evaluated at the proposed concentrations and times, dissolved in the different vehicles at pH 1.9 and 7.0, on F. nucleatum, P. intermedia, and P. gingivalis. The Kelsey-Maurer test was used to verify the presence or absence of colony-forming units. Each test was performed in triplicates with its respective viability controls. Results: Inhibition of F. nucleatum, P. intermedia, and P. gingivalis was achieved with TTC-HCl at all concentrations, dissolved in distilled water, saline solution, and 2% lidocaine with epinephrine 1:80,000 for all times. Conclusions: The results show that TTC-HCl is a good antimicrobial alternative against F. nucleatum, P. intermedia, and P. gingivalis regardless of the vehicle in which it was dissolved, concentration, pH, or time used in this investigation.